Economic and geographical analysis of small and medium enterprises development in the Brest region - Demyanov, Sergey (Human Geography Journal, 2017)
A comprehensive analysis of small and medium enterprises development level is illustrated using the example of theBrestregion. The statistical analysis of small and medium enterprises of the region is carried out. Based on the calculated indices the typology of administrative and territorial units of theBrestregion in terms of SMEs development is given. The component evaluation and rating of small and medium entrepreneurship in the context of the administrative districts is also represented in the study. The results of the component evaluation allow assessing the dynamics of small and medium-sized businesses development at the microregional level and classifying the administrative and territorial units.As a result of a comprehensive analysis of the small and medium enterprises economic and geographical consistent patterns of business development were identified. Spatial analysis of the small and medium enterprises development in theBrestregion has revealed the relative equability of the level of SMEs development. As it was predicted, the leading position according to the level of development is occupied by the cities and large surrounding districts.